Fluidisation of spherocylindrical particles: computational fluid dynamics–Discrete element method simulation and experimental investigation - Ling Zhou; Bo Wang; Yupeng Cao; Zhenjiang Zhao; Ramesh Agarwal (Engineering Applications of Computational Fluid Mechanics)
The fluidisation of spherocylindrical particles is often involved in the fields of biomass combustion, drug delivery and food drying. By spherocylindrical particles, we mean elongated spherical particles like non-spherical capsule pills and pulverised biomass fuels. Mastering the fluidisation state of spherocylindrical particles can improve the related industrial processes. In this paper, a coupled CFD–DEM method is used and the reliability of the model in this paper is verified with the help of high-speed photography experiments. Subsequently, the fluidisation characteristics of spherocylindrical particles in a spouted bed were investigated under different operating conditions and compared with the simulation results of spherical particles. The results show that the gas velocity influences the average bed height, axial velocity, volume fraction, orientation angle, and mixing mass of the particles. There are also significant differences in the fluidisation characteristics of particles at different bed heights. The particles in the higher bed region are more dispersed, the gas–solid mixing is more intense, and the gas velocity has a strong influence on the volume fraction/axial velocity of the spherocylindrical particles in the higher bed. In addition, this work also found significant differences in the fluidisation characteristics of different shaped particles.